Flow Shop Scheduling Theoretical Results, Algorithms, and Applications - Emmons, Hamilton; Vairaktarakis, George; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2013)
Although several monographs and edited volumes have discussed scheduling in general, most of these works survey the field by contributing a single chapter to production systems like flow shops. Flow Shop Scheduling: Theoretical Results, Algorithms, and Applications is solely dedicated to bringing together a huge body of knowledge on the subject, along distinct design features, in order to help scholars and practitioners easily identify problems of interest. This monograph has been organized into ten distinct flow shop systems and explores their connections. The chapters cover flow shop systems including two-machine, flexible, stochastic, and more. Outside of the traditional flow shops that require a job never revisits any stage, this book also examines the reentrant flow shop, in which a job may cycle back and be reprocessed at the same station or sequence of stations, multiple times. The authors have made the material accessible to a broad readership, using simplified notation and revealing unifying concepts. The results unique to flow shop research should provide the seed for research in other areas of scheduling and in optimization in general.
Introduction -- The Two-Machine Flow Shop -- Transfer Lags in the Flow Shop -- The m-Machine Flow Shop -- The Machine Flow Shop -- The Hybrid Flow Shop -- The No-Wait Flow Shop -- Blocking or Limited Buffers in Flow Shops -- Flexible Flow Shops -- Reentrant Flow Shops -- The Robust Flow Shops -- Stochastic Flow Shops -- The Complexity of Problems.
Keywords: Economics; Operations research; Economics/Management Science; Operation Research/Decision Theory; Operations Research, Management Science; Production/Logistics/Supply Chain Management